2009
DOI: 10.1167/iovs.08-2844
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Pattern of Neuroretinal Rim Loss in Ocular Hypertension

Abstract: The rate of RA loss (%/y) was greatest in the IT and ST sectors. However, because the nasal sectors contain more blood vessels (included in the HRT RA measurement), the percentage loss of neural tissue is underestimated in these sectors, to an unknown extent. The frequency of significant negative RA loss slopes was greatest in the ST, IN, and IT sectors. The finding suggests that all disc sectors should be evaluated for glaucomatous change in ocular hypertensive eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
(21 reference statements)
2
19
0
Order By: Relevance
“…Scanning laser ophthalmoscopy has been used for more than 20 years and longitudinal studies have explored its potential for detection of glaucoma progression. Although topography of rim area change has been found to be consistent with what is expected in glaucoma,29 30 rim area change has not always been associated with evidence of functional change 31 32. A study by our group found only fair correlation between functional and structural rates of change in a group of patients with suspected or definite glaucoma 32.…”
Section: Introductionsupporting
confidence: 50%
“…Scanning laser ophthalmoscopy has been used for more than 20 years and longitudinal studies have explored its potential for detection of glaucoma progression. Although topography of rim area change has been found to be consistent with what is expected in glaucoma,29 30 rim area change has not always been associated with evidence of functional change 31 32. A study by our group found only fair correlation between functional and structural rates of change in a group of patients with suspected or definite glaucoma 32.…”
Section: Introductionsupporting
confidence: 50%
“…This discrepancy may stem from several differences in study design. First, in previous studies, 7,20 eyes with ocular hypertension or glaucoma with high IOP were mainly enrolled, whereas in the present study 80% of the patients with mild glaucoma and 60% of the patients with 20 the spatial pattern of rim change was assessed longitudinally, whereas RNFL and rim were cross-sectionally evaluated in the present study. Third, the differences in rim detection methodology should also be considered; cup margin and disc margin as determined by Cirrus HD-OCT may differ from those detected by disc photograph or HRT.…”
Section: Discussionmentioning
confidence: 92%
“…Jonas et al 7 reported that glaucomatous rim loss assessed by disc photographs occurred in all sectors with regional preferences depending on the stage of the disease. Strouthidis et al 20 investigated the spatial pattern of longitudinal rim area decline by using the HRT and reported that the slopes of changes in nasal and temporal areas were less than those in superior and inferior areas. On the other hand, a study utilizing serial disc photographs reported that the main pattern of cup extension in eyes with ocular hypertension was generalized expansion, 6 which agrees with the present results; presently, the relative amount sectorial rim area and thickness loss showed even topographic distribution throughout all areas without spatial preference.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques, including confocal scanning laser ophthalmoscopy, scanning laser polarimetry, and optical coherence tomography, have improved the identification of early disease and also enhanced the observation of progressive optic nerve fiber loss over time (Figure 4). 3034 …”
Section: Methodsmentioning
confidence: 99%